Reading Metaphor of God in the Qur’an (al-Nūr [24]: 36) from Paul Ricoeur’s Theory of Metaphor - Nur Ahmad (Ulumuna, 2017)
This paper aims to demonstrate how the adoption of the theory of metaphor by Ricoeur to the “Light Verse” in the Quran. One of the most famous verse in the Quran is “the Light verse.” Beside the metaphor of light, the verse includes the metaphors of “the niche”, of “the lamp”, of “the glass”, and others. The metaphor “God is the Light” is the vital feature of the analysis. The next metaphors in the verse are an extension of that metaphor. The “light” metaphor with its principal meaning as “source” will be analyzed using the theory of metaphor as created by Paul Ricoeur in The Rule of Metaphor (1978). The application of this concept will unfold how this metaphor is employed creatively. It makes a parable of the gradation of lights and contains how it is widened to cover a broader aspect of faith, i.e., being the center and open to accept His light. The result of this experiment with metaphors in the Light verse shows fresh analysis that God illuminates on every creation in all realms.